2020
DOI: 10.1016/j.brachy.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of palliative interventional radiotherapy (brachytherapy) in esophageal cancer: An AIRO (Italian Association of Radiotherapy and Clinical Oncology) systematic review focused on dysphagia-free survival

Abstract: PURPOSE: The aim of this review was to examine efficacy of palliative interventional radiotherapy (IRT) in esophageal cancer compared with other treatment in terms of dysphagia-free survival (DyFS) and safety. METHODS AND MATERIAL: A systematic research using PubMed, Scopus, and Cochrane library was performed to identify full articles evaluating the efficacy of IRT as palliation in patients with esophageal cancer. ClinicalTrials.gov was searched for ongoing or recently completed trials, and PROSPERO was search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
2
18
0
1
Order By: Relevance
“…A brachytherapy boost was not implemented in the protocol, since this is not a standard therapy for the primary treatment of esophageal cancer. However, it can be a reasonable option for a local recurrence or symptom relief in a palliative situation [ 14 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…A brachytherapy boost was not implemented in the protocol, since this is not a standard therapy for the primary treatment of esophageal cancer. However, it can be a reasonable option for a local recurrence or symptom relief in a palliative situation [ 14 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…After SEMS placement, brachytherapy is the second most studied approach for the palliation of dysphagia in esophageal cancer [1,22,23]. Besides the SIREC trial, head-to-head comparison between SEMS and brachytherapy (in 3 fractions of 7 Gy) has been performed in one other RCT in 65 patients, which confirmed improved rapid dysphagia relief with SEMS after 1 month, but not at !3 months [24].…”
Section: Discussionmentioning
confidence: 96%
“…Lancelotta et al, in a metaanalysis, highlighted the safety and efficacy of radiotherapy over other modalities. Radiotherapy techniques are highly effective, leading to complete resolution of dysphagia in 87% of patients within one month, in two-thirds within three months, and in 50% of patients at six months after treatment [30]. Fuccio et al showed the effectiveness of brachytherapy and considered it the most effective treatment for malignant dysphagia.…”
Section: Discussionmentioning
confidence: 99%